Counter Ideology as a Method of Anticipation of Taqiyah in the Efforts of Deradicalization: a Study of the Bali Bombing Case I - Maulana, Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Terrorism is an extraordinary crime that causes enormous losses of property, life and body. Terrorism is often triggered by a radical understanding of religious teachings that are interpreted incorrectly.  The erroneous interpretation makes the perpetrators of terrorism view things outside the teachings they believe in as thagut and therefore must be eradicated. This makes the deradicalisation process for former terrorists very important. The deradicalisation process must be able to present the right understanding of religious arguments so that it can change the mindset and new perspective for former terrorists. Therefore, the deradicalisation process needs to use a method that touches the root of the problem of errors in interpreting religious propositions by terrorists.